Catch me if you can: how episodic and thematic multimodal news frames shape policy support by stimulating visual attention and responsibility attributions - Geise, Stephanie; Maubach, Katharina (Frontiers in Communication, 2024)
Using media coverage of animal welfare as an example, this study examines how the perception of multimodal news frames shapes recipients' visual attention, attributions of responsibility, emotions, and policy support. To investigate the mechanisms of multimodal-episodic versus thematic framing, we combined eye-tracking measurements with a pre-post survey experiment in which 143 participants were randomly assigned to an episodic or a thematic multimodal framing condition. The results show that episodic multimodal frames are viewed longer than thematic frames, elicit stronger individual and political responsibility attributions, and increase political support for stricter animal-welfare laws. Understanding multimodal framing as a multistep process, a serial mediation model reveals that episodic frames affect viewing time, which leads to stronger attributions of political responsibility and, in turn, stronger policy support. Our results support the idea of a complex interplay between subsequent stages of information perception and processing within a multimodal framing process.